Handbook of perceptual dialectology. - Preston, Dennis Richard (J. Benjamins, 1999)
Perceptual dialectology investigates what ordinary people (as opposed to professional linguists) believe about the distribution of language varieties in their own and surrounding speech communities and how they have arrived at and implement those beliefs. It studies the beliefs of the common folk about which dialects exist and, indeed, about what attitudes they have to these varieties. Some of this leads to discussion of what they believe about language in general, or "folk linguistics". Surprising divergences from professional results can be found. For the professional, it is intriguing to f.